Characterization of a Fusarium graminearum Salicylate Hydroxylase - Hao, Guixia; Naumann, Todd A.; Vaughan, Martha M.; McCormick, Susan; Usgaard, Thomas; Kelly, Amy; Ward, Todd J. (Frontiers in Microbiology, 2019)
Salicylic acid (SA) plays an important role in regulating plant defense responses against pathogens. However, pathogens have evolved ways to manipulate plant SA-mediated defense signaling. Fusarium graminearum causes Fusarium head blight (FHB) and reduces crop yields and quality by producing various mycotoxins. In this study, we aimed to identify the salicylate hydroxylase in F. graminearum and determine its role in wheat head blight development. We initially identified a gene in F. graminearum strain NRRL 46422 that encodes a putative salicylate hydroxylase (designated FgShyC). However, the FgShyC deletion mutant showed a similar ability to degrade SA as wild-type strain 46442; nor did overexpression of FgShyC in E. coli convert SA to catechol. The results indicate that FgShyC is not involved in SA degradation. Further genome sequence analyses resulted in the identification of eight salicylate hydroxylase candidates. Upon addition of 1 mM SA, FGSG_03567 (designated FgShy1), was induced approximately 400-fold. Heterologous expression of FgShy1 in E. coli converted SA to catechol, confirming that FgShy1 is a salicylate hydroxylase. Deletion mutants of FgShy1 were impaired but not blocked in SA degradation. Expression analyses of infected tissue showed that FgShy1 was induced during infection but virulence assays revealed that deletion of FgSh1 alone was not sufficient to affect FHB severity. Although the Fgshy1 deletion mutant did not reduce pathogenicity, we provide evidence that additional salicylate hydroxylases are present in F. graminearum and characterization of these enzymes will be necessary to fully understand the role of SA-degradation in FHB pathogenesis.